2018
DOI: 10.1002/jcp.26798
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding ribonucleic acid NKILA induces the endoplasmic reticulum stress/autophagy pathway and inhibits the nuclear factor‐k‐gene binding pathway in rats after intracerebral hemorrhage

Abstract: Long noncoding RNAs (lncRNAs) have emerged as an important class of molecules that have been associated with brain function and neurological disease, but the expression profiles of lncRNAs after intracerebral hemorrhage (ICH) remain to be elucidated. In this study, we determined the expression pattern of nuclear factor-k-gene binding (NF-kB) interacting lncRNA (NKILA) after ICH and examined its respective effects on the endoplasmic reticulum stress (ERS)/autophagy pathway, hippocampal neuron loss, and the NF-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Moreover, in type VII collagenase-induced intracerebral hemorrhage rats, silencing of lncRNA NKILA decreased neurological deficits, exacerbated hematoma and brain edema, and induced BBB breakdown, further leading to hippocampal neuron loss and inflammation cytokines production. The endoplasmic reticulum stress (ERS)/autophagy pathway and NF-κB signaling pathway were involved in this process (Jia et al, 2018). Dong et al (2018) found that lncRNA FENDRR regulated the vascular endothelial growth factor A (VEGFA)/miR-126 axis and contributed to the apoptosis of BMECs in hypertensive intracerebral hemorrhage mice models.…”
Section: Lncrnas In Intracerebral Hemorrhagementioning
confidence: 99%
“…Moreover, in type VII collagenase-induced intracerebral hemorrhage rats, silencing of lncRNA NKILA decreased neurological deficits, exacerbated hematoma and brain edema, and induced BBB breakdown, further leading to hippocampal neuron loss and inflammation cytokines production. The endoplasmic reticulum stress (ERS)/autophagy pathway and NF-κB signaling pathway were involved in this process (Jia et al, 2018). Dong et al (2018) found that lncRNA FENDRR regulated the vascular endothelial growth factor A (VEGFA)/miR-126 axis and contributed to the apoptosis of BMECs in hypertensive intracerebral hemorrhage mice models.…”
Section: Lncrnas In Intracerebral Hemorrhagementioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) is a subtype of non-coding RNAs with the transcripts of more than 200 nucleotides [11]. Although lncRNAs have no protein-coding capacity, they may regulate physiological functions as well as pathological processes in many diseases [12][13][14][15]. In particular, the activation of lncRNAs might regulate the expression of proteincoding genes through sophisticated mechanisms in ocular disorders [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are those which demonstrate no apparent protein-coding capacity and longer than 200 nucleotides [10]. Recent studies indicated a variety of regulatory functions of lncRNAs in a wide range of cellular and developmental processes as well as pathogenesis [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%